Transcriptomic, cytological, and physiological analyses reveal the potential regulatory mechanism in Tartary buckwheat under cadmium stress - Ye, Xueling; Li, Qiang; Liu, Changying; Wu, Qi; Wan, Yan; Wu, Xiaoyong; Zhao, Gang; Zou, Liang; Xiang, Dabing (Frontiers in Plant Science, 2022)
Rapid industrialization and urbanization have caused serious cadmium (Cd) pollution in soil. Tartary buckwheat is an important pseudocereal crop with the potential ability to tolerate various stresses. However, the responses to Cd stress in this species are unclear. In this study, we assessed the phenotypic, cytological, physiological, and transcriptomic characteristics of Tartary buckwheat under the various concentrations of Cd treatments to investigate the responses and their regulatory pathways for the first time. The results showed Tartary buckwheat could tolerate the high Cd concentration of 50 mg/L under Cd stress. The average root diameters increased as a result of more cell layers of the endodermis and the bigger size of the pericycle. Cd primarily accumulated in roots and relatively less transferred to leaves. Antioxidant activities and malondialdehyde (MDA) accumulation varied in different tissues and different Cd concentrations of treatments. Meanwhile, Cd stress led to the formation of Casparian strips in roots and damaged the cytoderm and organelles. The weighted gene co-expression and interaction network analyses revealed that 9 core genes induced by Cd stress were involved in metal ion binding, Ca signal transduction, cell wall organization, antioxidant activities, carbohydrate metabolic process, DNA catabolic process, and plant senescence, which regulated a series of phenotypic, cytological, and physiological changes above. These results laid the foundation for a deep understanding of the responses to Cd toxicity in Tartary buckwheat. It's also a critical reference for the functional characterization of genes for Cd tolerance.